Features of Corporate Liability for Violation of Competition Law - Yaroshenko, Oleg M.; Kutomanov, Dmytro Ye.; Maryniv, Nataliya A.; Dudenko, Tetiana V. (International Journal of Criminology and Sociology, 2022)
The relevance of the study is determined by the need to establish corporate responsibility for breach of legislation. In this regard, this paper is aimed at identifying features of competition and corporate responsibility for breach of competition law. Particular attention is drawn to the case when corporations become monopolists and, in fact, dictate market rules. Consideration of the development aspect of competition law suggests that it largely limits the growth of corporate business and forces corporations to formulate strategies for splitting the business, thereby determining the conduct of business. In the modern world, where business is in many respects globalised, such measures can lead to a decrease in market indicators and form a dependence on the operations of certain corporations in the local market. The leading method to the study of this issue is the modelling method, which allows to consider this problem as a targeted and organised procedure related to the improvement and application of competition law, as well as the protection and development of competition. The novelty of the study lies in the possibility of limiting the activities of a corporation in a market that is occupied by it and where there is no practical competition. The authors consider the mechanism of self-regulation as a source of domestic competition law. The paper determines that self-regulation processes are also subject to state supervision and thus corporate self-regulation becomes an aspect of the regulation of competition enforcement by the state at large. The practical significance of the study is determined by the structural feature of the corporation as a quasi-state mechanism and the regulation of external relations between the state and corporations as tax residents on this basis.